2005
DOI: 10.1162/0898929055002445
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Versus Contingent Mechanisms of Sensory-Driven Neural Biasing and Reflexive Attention

Abstract: Recent studies have generated debate regarding whether reflexive attention mechanisms are triggered in a purely automatic stimulus-driven manner. Behavioral studies have found that a nonpredictive "cue" stimulus will speed manual responses to subsequent targets at the same location, but only if that cue is congruent with actively maintained top-down settings for target detection. When a cue is incongruent with top-down settings, response times are unaffected, and this has been taken as evidence that reflexive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
54
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 28 publications
9
54
2
Order By: Relevance
“…Both components showed maximal response for sites located contralateral to the target side (hemisphere by target side significant interaction: F (1,15) ϭ 8.16, p Ͻ 0.05 for P1 and F (1,15) ϭ 8.67, p Ͻ 0.05 for N170). Consistent with previous reports in the literature (Mangun and Hillyard, 1991;Hopfinger and Ries, 2005), for both attention conditions, the P1 component was larger for valid conditions compared with invalid conditions when the target was presented in the contralateralvisualfield(supplementalmaterial,availableatwww. jneurosci.org).…”
Section: Erpssupporting
confidence: 90%
See 3 more Smart Citations
“…Both components showed maximal response for sites located contralateral to the target side (hemisphere by target side significant interaction: F (1,15) ϭ 8.16, p Ͻ 0.05 for P1 and F (1,15) ϭ 8.67, p Ͻ 0.05 for N170). Consistent with previous reports in the literature (Mangun and Hillyard, 1991;Hopfinger and Ries, 2005), for both attention conditions, the P1 component was larger for valid conditions compared with invalid conditions when the target was presented in the contralateralvisualfield(supplementalmaterial,availableatwww. jneurosci.org).…”
Section: Erpssupporting
confidence: 90%
“…Similar to previous studies (Mangun and Hillyard, 1991;Hopfinger and Ries, 2005), we found evidence for early sensory processing for validly cued compared with invalidly cued locations (indicated by a larger P1 component on valid trials). However, this difference was largely unaffected by cue predictability (Doallo et al, 2005).…”
supporting
confidence: 90%
See 2 more Smart Citations
“…The ADJAR filter was applied to the individual participant averages before participants' data were averaged together, as in previous studies (Hopfinger & Mangun, 1998Hopfinger & Ries, 2005;Hopfinger & West, 2006;McDonald & Ward 2000). Ten iterations of the ADJAR procedure were performed, and waveforms typically stabilized after 3-6 iterations, suggesting that the procedure was robust and effective.…”
Section: Recording and Analysismentioning
confidence: 99%